2020
DOI: 10.3390/cancers12061652
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Neoadjuvant Therapy in Colorectal Cancer Patients the Role of Messenger-and Micro-RNA Profiling

Abstract: Colorectal cancer patients’ responses to neoadjuvant therapy undergo broad inter-individual variations. The aim of this systematic review is to identify a molecular signature that is predictive of colon cancer downstaging and/or downgrading after neoadjuvant therapy. Among the hundreds analysed in the available studies, only 19 messenger-RNAs (mRNAs) and six micro-RNAs (miRNAs) were differentially expressed in responders versus non-responders in two or more independent studies. Therefore, a mRNA/miRNA signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 108 publications
(209 reference statements)
2
10
0
Order By: Relevance
“…Several gene expression signatures have been published [63][64][65][66][67]. In a recent review Izzotti et al summarized the current knowledge on genetic and epigenetic biomarkers used as predictors of response following nCRT [68]. After an extensive review of the literature, only 19 mRNAs and 6 miRNAs were found to be expressed differentially among responders versus non-responders in two or more independent studies.…”
Section: Assessment Of Response To Ncrtmentioning
confidence: 99%
“…Several gene expression signatures have been published [63][64][65][66][67]. In a recent review Izzotti et al summarized the current knowledge on genetic and epigenetic biomarkers used as predictors of response following nCRT [68]. After an extensive review of the literature, only 19 mRNAs and 6 miRNAs were found to be expressed differentially among responders versus non-responders in two or more independent studies.…”
Section: Assessment Of Response To Ncrtmentioning
confidence: 99%
“… 163 Several differentially expressed miRNAs in rectal cancer were reported as biomarkers that can predict response to nCRT. 164 , 165 For instance, expression level of miR-21, a well-characterized miRNA, was found to discriminate between complete responders and noncomplete responders in rectal cancer. 166 , 167 However, while one study demonstrated that overexpression of miR-21-5p was associated with complete regression after nCRT, 166 another study found the opposite.…”
Section: Introductionmentioning
confidence: 99%
“…EVs form includes microvesicles and exosomes that represent the common form of released extracellular miRNAs [30,65,68,69]. Nevertheless, miRNAs show the features of an ideal biomarker being available in body fluids, tissue-and disease-specificities, extremely stable and easily collected and detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR) [40,[76][77][78][79]. The identification of circulating miRNAs opened the possibility to use them as biomarkers to understand their role in human health or diseases [80].…”
Section: Circulating Mirnasmentioning
confidence: 99%